ASYMPTOMATIC INTESTINAL PROTOZOA IN SCHOOL AGE CHILDREN IN PATEGI, PATEGI LGA OF KWARA STATE, NIGERIA. - Adedoja, Ayodele Adeyemi; Akanbi II, Ajibola Aliu; Babatunde, Shola Kola (African Journal of Infectious Diseases (AJID), 2015)
Intestinal protozoan infection is one of the principal diseases contributing to human illness and suffering in tropical countries with significant effect of morbidity and mortality on children. The prevalence of intestinal asymptomatic protozoan infection was assessed (November, 2012 through May, 2013) among school age children in Pategi, Pategi Local Government area of Kwara State, Nigeria. Four public primary schools with nursery, prebasic and basic sections were used for the study. The age range was from 1 to 15 years old. Seven hundred and forty eight (748) stool specimens were collected and examined for protozoan cysts using the direct wet preparation and formol-ether concentration methods. One hundred and ninety seven (26.3%) of the samples were positive for intestinal protozoan parasite. The distribution of the parasites was E. histolytica/dispar (75.1), E. coli (18.8) and G. lamblia (6.1%). Balantidium coli cyst was not detected in the stool samples of the pupils. Highest prevalence of E. histolytica was observed among Gboke primary school (35.0%), closely followed by Nyamkpan (31.7%) and Sudan Interior Mission (SIM) (5.9%). Due males (28.0%) were more infection and female (24.7%), the difference was not statistically significant (P>0.05) except for G. lamblia infection (P<0.05). The public health implication of asymptomatic carriage of cyst of intestinal protozoan among low socioeconomic and sanitary standards of environments and children with poor personal hygiene was discussed. The use of mass chemotherapy and integrated measures of parasitic control would be of utmost importance in reducing the level of symptomatic infections among children.